INDUSTRIAL INVESTMENTS IN KERALA, TRENDS, CONSTRAINTS AND FUTURE PROSPECTS - SUNIL MANI (The Journal of Industrial Statistics, 2014)
Kerala is one of the least industrialised states although it has all the potential of being one. Historically speaking the state has attracted very little industrial investments especially in manufacturing. The problem has become even more acute over the last decade. The paper presents trends in industrial investments in Kerala and then attempts to provide an explanation of low investments in terms of four constraints: land, labour, environmental consciousness of the civil society and attitude of the bureaucracy. Given the constraints, the paper also delves into the type of service sector industries that the state may encourage.